Analisis Faktor-Faktor Yang Mempengaruhikredit Modal Kerja Perbankan Di Provinsi Kalimantan Selatan - Surbakti, Kristianto Satria; Syafrudin, Ruddy (PPJP ULM, 2019)
This study aimed to analyze the factors that influenced the working capital loansbanking in the province of South Kalimantan, with independent variables interest rate onworking capital loans, inflation rate in South Kalimantan Province, and rates of economicgrowth in the province of South Kalimantan. This study uses time series data from 2003-2017.The Analysis used are multiple regression with Ordinary Least Square (OLS).The result of this study indicate that the variable interest rates of working capitalloans have a significant effect on 5%,while economic growth have significant effect on 10%while inflation do not have the significant effect on working capital loan banking in SouthKalimantan Province.